IDENTIFIKASI MODEL PEMBIAYAAN USAHA KECIL DAN MENENGAH OLEH LEMBAGA KEUANGAN MIKRO DI KABUPATEN JEPARA - A. Khoirul Anam; Aida Nahar (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2015)
The development of Micro, Small and Medium Enterprises (SMEs) is determined by thepresence of microfinance institutions (MFIs) that offer financing models are diverse. Buton the other hand the diversity of models offered MFI financing has yet to be exploited.The objectives of the study was to identify the characteristics of business and financingneeds of SMEs, as well as identifying financing models that fit the character of SMEs. Theapproach used in this research is descriptive qualitative research through a case studyapproach, the informants in this study were employees and managers are authorized toprovide information on financing models. While the research conducted in the district ofJepara. Based on comparative models and characteristics of SME financing, MFIcooperative model provides relatively brief filing procedure with a low ceiling making itsuitable for small and micro businesses. As for MFIs BPR models have the advantage inproviding kinds of products are more varied and larger loan limit and interest ratesvaried so suitable for this type of small and medium enterprisesKeywods: SMEs, MFIs, financing model.